2017
DOI: 10.2334/josnusd.16-0833
|View full text |Cite
|
Sign up to set email alerts
|

The ball-on-disk cyclic wear of CAD/CAM machinable dental composite and ceramic materials

Abstract: The purpose of this study was to investigate the wear volume and the principal strain of machinable dental composite and ceramics in simulated mastication. A ball-on-disk wear test was performed for 3,000 cycles in water, using nine ball/disk combinations of three commercial CAD/ CAM materials: feldspathic, lithium disilicate glass ceramics, and a highly loaded composite material (n = 7 for each combination). The wear volume was optically measured using a digital scanner and analyzed for statistical difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
(29 reference statements)
0
3
0
2
Order By: Relevance
“…Occlusal antagonists were upper first premolars extracted for orthodontic or periodontal reasons without modifying the buccal cusp tip. (33)(34)(35) It was reported that extracted human enamel is more desirable for collecting information that may guide clinical practice. (36)(37)(38) Also, studies that didn't use enamel and used ceramics instead as antagonist, ignored the fact that the enamel roughens during wear more than the ceramic thus affecting further wear and abrasiveness to the opposing.…”
Section: Discussionmentioning
confidence: 99%
“…Occlusal antagonists were upper first premolars extracted for orthodontic or periodontal reasons without modifying the buccal cusp tip. (33)(34)(35) It was reported that extracted human enamel is more desirable for collecting information that may guide clinical practice. (36)(37)(38) Also, studies that didn't use enamel and used ceramics instead as antagonist, ignored the fact that the enamel roughens during wear more than the ceramic thus affecting further wear and abrasiveness to the opposing.…”
Section: Discussionmentioning
confidence: 99%
“…94 Sekonder çürüklerin kompozit rezinlerde en sık gözlenen başarısızlık türlerinden biri olmasından dolayı üreticiler bunu önlemek adına kompozit rezinlerin içerisine klorheksidin ve gümüş partikülleri eklemiştir. 96 Kompozit rezinlere gümüş nanopartiküllerin eklenmesinin biyofilm büyümesini azalttığı rapor edilmiştir. 95 Kompozitin aşınmasının doldurucu partikül ile ilişkili olduğu, özellikle doldurucu partikülün içeriği ve boyutuna ve rezin formülasyonuna bağlı olduğu bilinmektedir.…”
Section: • Adeziv Sistem Ve Kompozit Uygulama Yöntemiunclassified
“…Handa ve ark. 96 nanohibrit kompozitlerin Knoop sertlik değerini mikrofil kompozit rezinden daha fazla olarak Son 10 Yılda Kompozit Rezin Restorasyonlar: İn Vivo ve İn Vitro Çalışmalarla Bir Derleme bildirmişlerdir. Sınıf I kavitelerde yapılan çalışmada nanohibrit kompozitin mikrofil kompozitten istatiksel olarak anlamlı şekilde daha az aşınma gösterdiği rapor edilmiştir.…”
Section: • Adeziv Sistem Ve Kompozit Uygulama Yöntemiunclassified
“…The variation of hardness values between all composite restoratives surfaces can clarify the variation in the rate of wear. Consequently, it found that the wear of restorative materials is determined by some factors, especially the hardness of the restorative material [15]. Both the surface roughness value and wear affected the strength of the resultant composites that was increased with a decrease of surface roughness and has significant differences for the same surface roughness values with different directions of scratch [16].…”
Section: Introductionmentioning
confidence: 99%